2020
DOI: 10.2478/revecp-2020-0021
|View full text |Cite
|
Sign up to set email alerts
|

Competitiveness in the European Consolidated Banking Sector After the 2008 Financial Crisis

Abstract: The constitutional conception of market integration within the European Union entails creating a level playing field for competition in the consolidated banking sector. The financial crisis of 2008 brought with it the need to proceed with care as it rolled back the gains of improving competitive conditions in the financial sector. Even though a lot of studies have investigated competitive conditions prior to the crisis, the same cannot be said of periods after the crisis. Using both structural and non-structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Meanwhile, cost reduction can be made by replacing a more efficient management system, implementing low-cost technology and business, and producing a product mix that provides economies of scope and economies of scale (Tremblay & Tremblay, 2012;Van Hoose, 2010). A study of bank mergers in the United States from 1985 to 1996 found that the increase in stock prices of consolidated banks was due to cost savings rather than anticipated increases in income (Klutse, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Meanwhile, cost reduction can be made by replacing a more efficient management system, implementing low-cost technology and business, and producing a product mix that provides economies of scope and economies of scale (Tremblay & Tremblay, 2012;Van Hoose, 2010). A study of bank mergers in the United States from 1985 to 1996 found that the increase in stock prices of consolidated banks was due to cost savings rather than anticipated increases in income (Klutse, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…These factors are activated in circumstances of crisis, namely the crisis that the banking sector has faced since 2008 with devastating consequences for employees. In addition, massive lay-offs (Tarki et al, 2020), high results control systems in financial operations (Altavilla et al, 2020), increasing competitiveness to attract financial resources (Klutse, 2020), long working hours until objectives are reached (Sanusi et al, 2020) and high turnover in positions and offices (Sudria, 2016;Kurdi and Alshurideh, 2020;Yukongdi and Shrestha, 2020) have been identified.…”
Section: Stress At Workmentioning
confidence: 99%
“…In Spain, banking has experienced a 54.4% reduction in financial entities from 2008 to 2020 (CCOO, 2020). High unemployment rates and job insecurity have ended up affecting competitiveness in the banking system (Barroso, 2017;Klutse, 2020). The impact that the closure of offices has had on the well-being, personal stability and health of employees has been devastating (Cortès-Franch and López-Valcárcel, 2014).…”
Section: Introductionmentioning
confidence: 99%